ANALISIS PENGARUH LABEL HALAL, KEAMANAN BAHAN, PROMOSI, DAN HARGA PADA PRODUK KOSMETIK SARIAYU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada Mahasiswi Fakultas Ekonomi Dan Bisnis Angkatan 2015-2018 Universitas Islam Malang) - Khumairotul Khuwaroh; Agus Widarko; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to examine and analyze the influence of halal labels, material safety, promotion and prices on consumer purchasing decisions. Population and sample were 100 respondents who had used Sariayu cosmetic products. Data collection through questionnaires. Data analysis in this study uses SPSS version 14. Testing the application of data used in this study include validity test, reliability test, normality test, heterocedestity test, multicollinearity test, F test and t test. The results of the analysis show that halal labels, material security, promotion and prices have a positive effect on consumer purchasing decisions. The results of the t test show a significance value > 0.05, therefore the halal and price label variables have a significant effect on consumer purchasing decisions. While the material and promotion security variables show a significance value of <0.05, therefore the material and promotion security variables are stated to have no significant effect on consumer purchasing decisions Keyword: Halal labels, Ingredients safety, Promotion, Price, Buying decision